The shift in forest and tree limits in Troms County - with a main focus on temperature and herbivores - Normark, Kristoffer (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2012)
To better understand how various factors affect the establishment of forest and trees around the tree line-ecotone, this study was conducted in Troms County, Norway. The altitude of different forest and tree limits together with the surrounding vegetation type were collected during August 2011. Comparisons of the collected data were made with previously collected data from the same sites conducted 1914 and 1915. On average the forest limit has expanded with 26 meters in altitude, however, an expansion is not statistically significant for the whole area. The tree limit has significantly expanded in altitude. At all weather stations the temperature sum and length of the growing season have increased which is proposed to have positive effects on sapling establishment. There is no significant correlation between the change in sheep density in relation to the shift in forest and tree limit. The shift in reindeer density did not correspond to the shift of forest limit, but to the shift in tree limit. However the coefficient of determination was low which means that reindeer only accounts for a small part of the altitudinal shift. At many sites where the tree limit has expanded, reindeer density has declined which might have provided for new plants to establish and older to grow in size. The altitude of the forest and tree limits increases with increasing distance to the coast, most likely due to the degree of maritimity. It should also be noted that the magnitude of the shift in the limits, decrease with increasing distance to the coast. With reduced amount of reindeers and increased temperature vegetation changes have occurred. The amount of birch forest has increased, most likely, in expense of declined willow-thickets. Also abundance of alpine lichen/moss heath has increased, which might be a result of reduced grazing by reindeers.